2018
DOI: 10.1016/j.jtho.2018.08.1491
|View full text |Cite
|
Sign up to set email alerts
|

P2.16-16 SABRTOOTH: A Fasibility Study of SABR Versus Surgery in Patients with Peripheral Stage I NSCLC Considered to be at Higher Risk for Surgery

Abstract: patients treated with linear accelerator-based SABR between 2009 and 2016 were retrospectively studied. Impact of patient, tumor, and treatment parameters on LC, OS and toxicity-free survival (TFS) were evaluated by multivariate analyses. Result: Forty-eight PL and 22 OM lesions were analyzed, including 20 (28%) re-irradiation (Re-RT) cases. Median total, fractionated, and biological equivalent doses in BED10 and BED3 were 55 (30-60), 9.75 (4-18), 110 (41-151), and 228 (90-378) Gy, respectively. Doses given as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Although current treatment guidelines do not recommend SABR as first-line treatment for NSCLC moderate risk patients(1), multiple observational studies have suggested therapeutic equipoise exists between SABR and surgery in those patients with multiple comorbidities (8,9). The lack of long term QoL data from these two treatments has highlighted the importance of understanding whether a truly informed "shared treatment decision" between patients and clinicians can be made.…”
Section: Introductionmentioning
confidence: 99%
“…Although current treatment guidelines do not recommend SABR as first-line treatment for NSCLC moderate risk patients(1), multiple observational studies have suggested therapeutic equipoise exists between SABR and surgery in those patients with multiple comorbidities (8,9). The lack of long term QoL data from these two treatments has highlighted the importance of understanding whether a truly informed "shared treatment decision" between patients and clinicians can be made.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled trials (RCTs) are seen as the highest quality of evidence, because the randomization process can prevent bias [5]. Some RCTs that compared SBRT to VATS resection in operable patients have been discontinued due to low patient accrual [6][7][8]. A pooled analysis of two discontinued RCTs suggested equal effectiveness, although small sample size and short follow-up prohibited definitive conclusions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although current treatment guidelines do not recommend SABR as first-line treatment for Non-Small Cell Lung Cancer (NSCLC) moderate risk patients [1], multiple observational studies have suggested therapeutic equipoise exists between SABR and surgery in those patients with multiple comorbidities [8,9]. The lack of long term QoL data from these two treatments has highlighted the importance of understanding whether a truly informed, shared treatment decision between patients and clinicians can be made.…”
Section: Introductionmentioning
confidence: 99%